SOCIAL ECONOMIC ANALYSIS OF BUMPERS AND BEGGERS IN MEDAN CITY POST COVID-19 PANDEMIC - Nurmayana Siregar; Fatimah Zahara (Proceeding International Seminar of Islamic Studies, 2022)
The purpose of the study was to determine: 1.Characteristics, Working Mechanisms of Homeless and Beggars (GEPENG) in Medan City. 2. The Influence of Socio-Economic Factors on the Reasons for Being GEPEENG. 3. GEPENG Handling Solutions After the Covid-19 Pandemic. Research Data Analysis: a. Analytical Descriptive Method b. Multiple Linear Regression Method. Research Results: From the Partial Test, it is known: 1. The results of data processing from 75 respondents, show that: The GEPENG are generally of Productive Age: 15-64 years, with elementary education: 38.67% and are not entirely residents of the city of Medan. But came from several other cities such as: Belawan City: 16.00%. Their income is Rp. 26.000 Rp. 30,000 per day and support 1-4 family members. They live with poverty and pass it on to their children and grandchildren. So there was a GEENG nursery. But with the existence of a Client Relationship Patron, it makes them feel more comfortable and comfortable being BUMPED. 2. Socio-Economic Factors have a significant influence on the reasons for becoming GEPENG (Accept H1). Because all the calculated T values are greater than the T table and the probability / significance is far below 0.05. Simultaneous test shows that: Adjusted R2 = 0.816. This means that 81% of the reasons for being GEPENG are caused by socio-economic factors, while another 19% are due to other factors. 3.a). Handling GEPENG is not only the responsibility of the government, but the participation of the community is highly expected. Empowerment of Potential and Social Welfare Resources (PSKS) which is more optimal. 3.b). UPTD Panti Karya Binjai with a work program has succeeded in transmigrating GEPENG to various regions, but with limited funds and facilities and human resources, it is still considered less than optimal. Because the ability of the Social Institution is not proportional to the fast growth rate of the number of GEPEENG. 3.c). Law enforcement is needed, namely the implementation of the Criminal Code Articles 504 and 505 and the existence of a Regional Regulation after the Covid-19 Pandemic